Decentralisation and drought adaptation: applying the subsidiarity principle in transboundary river basins. Issue 1 (March 2018) - Garrick, Dustin E.
Determining how to adapt to freshwater scarcity and variability has become an important question for institutional analysis and development. This paper addresses the assignment challenge in drought adaptation, namely the challenge of assigning and coordinating governance responsibilities across nested levels of social organisation. The subsidiarity principle suggests that adaptation decisions and associated governance responsibilities should occur at the lowest level at which they can be performed competently. Droughts and related slow-onset 'shocks' throw into question which level is lowest, and how this varies with the duration, severity and extent of the event. This paper explores the potential for the subsidiarity principle to guide the assignment and assessment of governance responsibilities associated with drought adaptation. It reviews literature at the intersection of common pool resource studies and new institutional economics to elaborate four diagnostic questions: (1) what are the opportunities and limits of decentralised (independent) drought adaptation?; (2) how are social dilemmas and spillovers associated with drought adaptation managed?; (3) when do higher level institutions complement versus crowd out decentralised adaptation?; and (4) how does adaptation by individuals and groups affect adaptive efficiency? An illustrative comparison of drought adaptation in the US portions of the Colorado and Rio Grande Rivers of North America demonstrates: (i) the potential and limits of decentralised adaptation through urban water conservation and irrigation efficiency, (ii) the importance of both formal and informal coordination institutions (e.g. river basin organisations) to address cross-border externalities, including conflicts and economies of scale, and (iii) the pivotal role of groundwater management for adaptive efficiency, requiring a balance between local, short-term dependence on groundwater for drought adaptation with transboundary, long-term outcomes caused by unsustainable extractions.